The impact of COVID-19 lockdown on soccer positional and physical demands in the Spanish La Liga - Garcia-Calvo, T.; Fernandez-Navarro, J.; Diaz-Garcia, J.; Lopez-Del Campo, R.; Fernandez, F. M.; Memmert, D. (Science and Medicine in Football, 2023)
The present study aimed to analyse the playing surface area, dispersion and distance covered of professional football teams comparing the pre-lockdown and post-lockdown periods. Positional and match physical demands data were collected from all matches played in the First Spanish Division (n = 760) during season 2019/2020. Pre-lockdown (1st-27th matchday) and post-lockdown periods (28th-38th matchday) were compared. Variables related to team-level spatial (i.e., convex hull, team width and team length) and physical performance (i.e., total distance and high-speed running distance) were analysed using an optical tracking system (i.e., ChyronHego). In addition, these variables were concerned with respect to the match location contextual variable. Linear mixed models were used to examine the difference between the pre-lockdown and post-lockdown periods following a hierarchical structure considering players, matches and teams. The results revealed that the pandemic lockdown affected the teams` performance when comparing the periods before and after lockdown, showing a general decrease in the average values of the spatial and physical variables measured. The current data could assist practitioners in making informed decisions in order to design and improve training plans for similar situations in which teams return to competition after an unusual period with no training.